2016
DOI: 10.1111/ehr.12332
|View full text |Cite
|
Sign up to set email alerts
|

Migrants’ self‐selection in the early stages of modern economic growth, Spain (1880–1930)

Abstract: Drawing on a large database from the register of inhabitants of Madrid, this article confirms that the literacy levels of internal migrants moving to the Spanish capital city in the late nineteenth and early twentieth century were higher than that of those who remained in their provinces of origin. This article also explores the different factors influencing the nature and intensity of the selection process. The empirical exercise stresses that the stock of previous migration was a fundamental factor in allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 35 publications
0
4
0
3
Order By: Relevance
“…An important feature absent from our analysis is internal migration, which could affect the stock of human capital. Beltrán Tapia and Miguel Salanova (2017) found that the migrants moving to Madrid from 1880 to 1930 were on average more literate than their counterparts who remained in their provinces of origin. Other destinations, however, attracted fewer literate migrants, especially those moving from rural areas to the provincial capital, often resulting in negative self-selection.…”
Section: A Regional Perspective On Age-heaping and Literacy In Spain ...mentioning
confidence: 99%
“…An important feature absent from our analysis is internal migration, which could affect the stock of human capital. Beltrán Tapia and Miguel Salanova (2017) found that the migrants moving to Madrid from 1880 to 1930 were on average more literate than their counterparts who remained in their provinces of origin. Other destinations, however, attracted fewer literate migrants, especially those moving from rural areas to the provincial capital, often resulting in negative self-selection.…”
Section: A Regional Perspective On Age-heaping and Literacy In Spain ...mentioning
confidence: 99%
“…Studies based on census data typically use measures of status derived from recorded occupations to infer migrant selection (Abramitzky, Platt Boustan, & Eriksson, 2013;Long, 2005;Salisbury, 2014). Alternative approaches to occupational measures have approximated human capital by using heights, literacy, or numeracy (Beltrán Tapia & de Miguel Salanova, 2017;Humphries & Leunig, 2009). The results, depending on context, are mixed.…”
Section: Measuring Gains To Migration In the Pastmentioning
confidence: 99%
“…El trabajo doméstico se comercializó de manera 34 Crossick y Haupt, 1995. 35 Nielfa, 1985y De Miguel, 2017. 36 Baker, 2009.…”
Section: Factores Determinantes En Los Procesos De Integración De Natunclassified
“…4 Boyer y Hatton, 1994y 1997, Boyer, 1997, Grant, 2005 y Beine, Docquier y Özden, 2011. 5 Paluzie, Pons, Silvestre y Tirado, 2009; Silvestre, Ayuda y Pinilla, 2015; Carballo y Vicente, 2017 y Beltrán y De Miguel, 2017. comercial excesivamente atomizada. El primer tercio de la siguiente centuria generó, sin embargo, cambios sustanciales en este panorama.…”
unclassified